Interim Analysis of Baseline Characteristics and Preferences of Administration Route of Rheumatoid Arthritis Patients Who Are Bio-Naive or Switched between Advanced RA Treatments; A Multicenter, Prospective, Observational Study - Direskeneli, Haner; Karadag, Omer; Ates, Askin; Tufan, Abdurrahman; Inanc, Nevsun; Koca, Suleyman Serdar; Gunay, Levent Mert (Wiley, 2018)
[Abstract Not Available]
Annual Meeting of the American-College-of-Rheumatology (ACR) and Association-for-Rheumatology-Health-Professionals (ARHP) -- OCT 19-24, 2018 -- Chicago, IL